Deficiency of Mutual Trade between Kazakhstan and the EAEU Countries: Trends and Dominant Factors - V. Yu. Dodonov (Евразийская интеграция: экономика, право, политика, 2021)
The article analyzes trends and factors in the dynamics of Kazakhstan’s mutual trade within the EAEU with an emphasis on imports and trade deficits. The aim is to identify the relationship between changes in the absolute and relative values of these parameters and the country’s membership in Eurasian integration organizations and with more general external factors. To achieve the aim, the volume, dynamics and share of imports and trade deficits are analyzed in the context of changes in the purchasing power of the population, world oil prices and volumes of Kazakhstan’s foreign trade with the rest of the world. Research methods: comparative analysis of time series, structural and correlation analysis. As a result of the analysis, a tendency was revealed for an increase in the imbalances in mutual trade of Kazakhstan during the EAEU existence, which, however, are far from historical highs, which does not allow us to conclude that there is a causal relationship between the country’s membership in this association and the aggravation of problems in mutual trade. On the other hand, it was revealed that significant shifts in the share of imports from the EAEU countries to Kazakhstan and the resulting changes in the trade deficit occurred during periods of significant shifts in the purchasing power of the population and are inversely proportional. The analysis made it possible to draw the following conclusions: the relative indicators of imports and trade deficits do not show growth after the creation of the EAEU; the main factor in the change in the share of imports to Kazakhstan from the EAEU is the dynamics of the currency equivalent of household income — the increase in the share of imports from the EAEU occurs during periods of decline in household income, and its decline during periods of their growth; the currency equivalent of income in Kazakhstan is closely correlated with world oil prices, that is, the dependence of the parameters of imports from the EAEU and the trade deficit is due to a more general factor in the external economic situation that affects the purchasing power of the population and business.